El cuerpo contra la pared : representaciones del cuerpo en la imagen grafiti - Vargas Rodríguez, Alberto (Bogotá : Editorial UTADEO, 2017)
The body against the wall is a reading of the representations of the human body in the graffiti image with the lenses of the history of art, aesthetics, sociology and literature; Explored with the purpose of trying to understand something of the contemporary social and cultural universe. Within the wide spectrum of the graffiti image stands a prolific slope in which the motive of primordial representation is the human body. Painted, stenciled, adhered on the walls, these images are ephemeral tattoos in urban skin; In them the body becomes a form of language through which they range from advertising messages to diatribes on the status quo, and from individual opinions and desires to collective imaginaries.
La ciudad contemporánea -- El cuerpo femenino -- El cuerpo masculino -- El cuerpo político -- El cuerpo artístico -- Otros modelos del cuerpo -- Representaciones del otro y de sí mismo.
Incluye referencias bibliográficas (páginas 295-303).
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2021. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Street art; Arte callejero; Pintura y decoración mural -- Siglo XX; Figura humana en el arte; Mural painting and decoration -- 20th century; Graffiti; Human figure in art; Libros electrónicos.